How is the understanding of Village Financial Statements affected by the Level of Education and Work Experience ? - Muhammad Natsir (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The goal of this research is to look into and evaluate the effect of academic and government employment experience on comprehension of village reports on finances. The aforementioned study's sample consisted of 40 village leaders from Tanantovea District. For this study, the town's Chief/Village Secretary, Chief of Finance, Chief of Planning, and Head of Administration and Administrative Matters were all questioned. Data collecting strategies include providing questionnaires to respondents, and the analytic approach employed is multiple linear regression. The outcomes of this According to research, the degree of educational attainment and work experience simultaneously have a substantial influence on the interpretation of local financial reports. The degree of education has a considerable impact on the comprehension of village financial reports. and job experience has a substantial influence on comprehension of village financial reports